2021
DOI: 10.1002/ajb2.1594
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding in Solanum carolinense alters floral attractants and rewards and adversely affects pollinator visitation

Abstract: Inbreeding depression is well documented in flowering plants and adversely affects a wide range of fitness-related traits. Recent work has begun to explore the effects of inbreeding on ecological interactions among plants and other organisms, including insect herbivores and pathogens. However, the effects of inbreeding on floral traits, floral scents, and pollinator visitation are less well studied. METHODS: Using inbred and outbred maternal families of horsenettle (Solanum carolinense, Solanaceae), we examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 72 publications
(118 reference statements)
1
17
0
Order By: Relevance
“…In summary, our research on S. latifolia suggests that in addition to inbreeding disrupting interactions with herbivores by changing plant leaf chemistry (Schrieber et al, 2018) it affects plant interactions with pollinators by altering flower chemistry. Our observations are in line with studies on other plant species (Ivey and Carr, 2005;Kariyat et al, 2012Kariyat et al, , 2021 and highlight that inbreeding has the potential to reset the equilibrium of species interactions by altering functional traits that have developed in a long history of co-evolution. These threats to antagonistic and symbiotic plant-insect interactions may mutually magnify in reducing plant individual fitness and altering the dynamics of natural plant populations under global change.…”
Section: Main Textsupporting
confidence: 91%
See 3 more Smart Citations
“…In summary, our research on S. latifolia suggests that in addition to inbreeding disrupting interactions with herbivores by changing plant leaf chemistry (Schrieber et al, 2018) it affects plant interactions with pollinators by altering flower chemistry. Our observations are in line with studies on other plant species (Ivey and Carr, 2005;Kariyat et al, 2012Kariyat et al, , 2021 and highlight that inbreeding has the potential to reset the equilibrium of species interactions by altering functional traits that have developed in a long history of co-evolution. These threats to antagonistic and symbiotic plant-insect interactions may mutually magnify in reducing plant individual fitness and altering the dynamics of natural plant populations under global change.…”
Section: Main Textsupporting
confidence: 91%
“…The chemodiversity and abundance of floral VOC involved in communication with H. bicruris moths was reduced in a sex- and origin-specific manner in inbred relative to outbred S. latifolia ( Figure 2e–g ), while the full floral scent profile exhibited no differences among inbreds and outbreds ( Figure 2—figure supplement 2 ). So far, lower emissions of floral VOC in inbreds have been reported for only few plant species pollinated by diurnal generalists ( Ferrari et al, 2006 ; Haber et al, 2019 ; Kariyat et al, 2021 ). Our study revealed such effects for plants pollinated by specialist moths that use scent as a major cue for plant location ( Riffell and Alarcón, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Solanum-type flowers have evolved across Primilaceae, Gesneriaceae, and Ericaceae, in addition to Solanaceae with typical characteristics of buzz-pollinated species. These include the presence of poricidal anthers and the lack of nectar or other pollen rewards, which dispense pollen only to the authorized buzz pollinators [2,[5][6][7]. Flowers from most of the Solanum spp.…”
Section: Introductionmentioning
confidence: 99%